Apple pomace silage ethanol intake and its effect on sheep (Bangladesh Journal of Animal Science, 2014)
Two experiments were undertaken to investigate the feeding effect of alcoholic apple pomace silages (APSs) on performance traits, ruminal pH and blood variables in sheep. In experiment 1, four ewes were fed alfalfa hay cube and either APS (ethanol content was 33.4 g /kg DM) or concentrate (control) at a ratio of 30:70 of TDN requirement for maintenance and daily 100g gain in a 2×2 crossover design over two 35-day periods. Total body weight gain was higher in control treatment. No significant treatment effect was observed for TDN intake and ruminal pH. Plasma concentrations of ethanol, lactate and ?-hydroxybutyrate (BHBA) were increased after feeding APS. Plasma insulin, glucose, glutamate oxaloacetate transaminase (GOT) and glutamate pyruvate transaminase (GPT) were not significantly differ between the treatments. The area upper or under curves (AUCs)of plasma ethanol and BHBA were greater and lactate was tended to greater in APS treatment. In experiment 2, low and high ethanol contained APSs (L-APS, 44.1g and H-APS, 66.9 g of ethanol/kg DM) were compared in the same design (Experiment 1). No significant treatment effect was observed for body weight gain and TDN intake. Pre-feeding ruminal pH was lower in L-APS treatment. Insulin concentration was slightly higher in L-APS treatment. However, no significant treatment effect was detected for other variables. According to the consistent increase in plasma ethanol, lactate and BHBA, and the plasma AUCs response of ethanol, lactate and BHBA after feeding of alcoholic-fermented APSs, it would be concluded that APS ethanol consumption affect the post prandial blood metabolism as well as influenced the plasma lactate and BHBA concentrations in the blood.DOI: http://dx.doi.org/10.3329/bjas.v43i3.21655 Bang. J. Anim. Sci. 2014. 43 (3): 224-231